GOVERNMENT AND BUSINESS PARTNERSHIP:: SEARCH FOR A STRATEGIC PROSPECT - V. Bikeeva, Marina (Gênero & Direito, 2020)
The research is important due to insufficient elaboration of theoretical aspects in the field of cooperation of the governmental agencies of various layers and the business organizations assuring the balanced economic, social and environmental development of the society. In view of this, this article is aimed at setting forth and substantiating a scientific idea about mutually-advantageous partnership of the interested groups with account taken of qualitatively new regularities of the phenomenon researched. The article is aimed at substantiating the necessity of a mechanism of the government and business cooperation on the basis of a strategic partnership assuring the development and strengthening of the long-term relations with the interested parties, the focus on the corporate social responsibility and on the society problems. The leading approach to researching this problem is a systemic approach oriented toward formation and maintenance of the long-term relations of the government agencies and the business organizations. The offered transformations outcome is a modern mechanism of social relations between the government and the business, which is designed to efficiently solve issues of the national (including regional) social and economic growth. The article materials are of practical value to develop the regional management strategy that is oriented toward the long-term sustainable development with account taken of the global tendencies assuring the balanced economic, social and environmental development of the society.